Study of temperature influence on seed and seedling vigour in medium seeded chickpea for rice based cropping system - Naik3 and P.K. Patra4, Suneeta Patra1*, R.N. Sharma2, M.L. (Journal of Experimental Sciences, 2011)
The seed size of chickpea plays greater role in establishing a good chickpea crop after the rice. Small seeded chickpea varieties have greater potential as compared to the bold seeded ones under the rice based cropping system. Results of temperature influence on seed and seedling vigour in medium seeded chickpea for rice based cropping system revealed that 25o C to 30o C temperature was found optimum for various seed/seedling vigour parameters from one hand and on the other hand differential varietal performance noted for the different seed/seedling vigour parameters. Implications of these findings have been discussed in the paper.